STATE OF DEVELOPMENT OF FIBER PRODUCTS – CLEANING, COMBING TECHNIQUES AND TECHNOLOGIES - Inoyatova, Maftuna; Ergasheva , Shaxzoda; Kamalova , Iroda; Toshpo’latov , Mansurxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: Cotton fiber is the most valuable for the textile industry within natural fibers. The products made from it are far superior to other textiles in their ecological purity, high absorbing water. The high quality of yarn fabrics is primarily due to the externalization of the processes of grinding and cleaning cotton fibers in spinning enterprises. The purpose of the grinding process is to prepare the cotton fiber for cleaning, mixing, and provide an opportunity for the returns to be processed.